EKSPLORASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN: ANALISIS KONTEN TIKTOK @marhaban.academy DENGAN KURIKULUM MERDEKA - Kyla Raissa; Tatang Tatang; Mia Nurmala (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The TikTok application is increasingly being used as an alternative learning medium, including for Arabic language learning. However, Arabic language learning content on TikTok is not necessarily aligned with the current curriculum, potentially failing to support learning needs in schools. Therefore, this study aims to analyze the suitability of Arabic language learning content on the TikTok account @marhaban.academy with the Arabic Language Learning Outcomes (CP) for Phase F of the Merdeka Curriculum, which comprises two main components: language skills (maharah) and essential material related to daily life. The method employed is content analysis with a descriptive qualitative approach, following Klaus Krippendorff's analytical stages and utilizing Fenwick W. English's (1992) Curriculum Alignment Theory framework as a benchmark for determining suitability. The classification into "suitable," "partially suitable," and "not suitable" categories refers to the reflection of the Phase F CP components. The analytical stages were carried out through the collection and selection of representative content, coding of the content using a coding sheet based on the Phase F CP components, data reduction into suitability categories, and systematic conclusion drawing. Of the total 240 contents classified into 10 categories, the results showed that 138 contents were categorized as suitable, 97 as partially suitable, and 5 as not suitable. These findings indicate that the TikTok account @marhaban.academy serves as a supplementary Arabic language learning medium that is aligned with the Merdeka Curriculum. It can be utilized by teachers as a reference for learning media in the classroom and by students as an independent learning resource outside the classroom, particularly through its vocabulary and daily expression content, which most consistently reflects the Phase F CP components. ABSTRAK Aplikasi TikTok semakin umum digunakan sebagai alternatif media pembelajaran, termasuk dalam pembelajaran bahasa Arab. Namun, konten pembelajaran bahasa Arab di TikTok belum tentu memiliki keselarasan dengan kurikulum yang berlaku, sehingga berpotensi tidak mendukung kebutuhan pembelajaran di sekolah. Oleh karena itu, penelitian ini bertujuan untuk menganalisis kesesuaian konten belajar bahasa Arab pada akun TikTok @marhaban.academy dengan Capaian Pembelajaran (CP) bahasa Arab Fase F Kurikulum Merdeka yang mencakup dua komponen utama, yaitu keterampilan bahasa (maharah) dan materi esensial kehidupan sehari-hari. Metode yang digunakan adalah analisis konten dengan pendekatan kualitatif deskriptif, mengikuti tahapan analisis Klaus Krippendorff dan kerangka Curriculum Alignment Theory Fenwick W. English (1992) sebagai tolok ukur kesesuaian. Penentuan tingkat sesuai, sesuai sebagian, dan tidak sesuai mengacu pada refleksi komponen CP Fase F. Tahapan analisis dilakukan melalui pengumpulan dan pemilihan konten representatif, pengkodean konten menggunakan lembar koding berbasis komponen CP Fase F, reduksi data ke dalam kategori kesesuaian, hingga penarikan simpulan secara sistematis. Dari total 240 konten yang terbagi ke dalam 10 kategori, diperoleh hasil sebanyak 138 konten dikategorikan sesuai, 97 sesuai sebagian, dan 5 tidak sesuai. Temuan ini menunjukkan bahwa TikTok @marhaban.academy berperan sebagai media pembelajaran bahasa Arab pendamping yang selaras dengan Kurikulum Merdeka dan dapat dimanfaatkan oleh guru sebagai referensi media pembelajaran di kelas maupun oleh pelajar sebagai sumber belajar mandiri di luar kelas, khususnya melalui konten kosakata dan ungkapan sehari-hari yang paling konsisten mencerminkan komponen CP Fase F.